Descriptive analysis of Olympic class windsurfing competition during the 2017-2018 regatta season. (4th July 2019) - Anastasiou, Alex; Jones, Thomas; Mullan, Paul; Ross, Emma; Howatson, Glyn
ABSTRACT: The aim of the present study was to describe race characteristics of the top three finishers for different wind speed categories within Olympic windsurfing competition. Global position system data was analysed from 94 races (47 Men's races & 47 Women's races) across five regattas during the 2017–2018 windsurfing season. Medium wind speeds (8.1 to 15.9 knots) represented the greatest proportion of races for Men (43%) and Women (34%). Large variations in race time (825–2105 s), distance (2167–11, 786 m) and board speeds (3.32–16.78 kts) were experienced across the wind categories. Although race time for Women was non-significant ( P = 0.101) between wind categories. Low first windward mark position was reported in both Men (first = 2.2 ± 2.1, second = 3.7 ± 2.6, third = 5.0 ± 3.3) and Women (first = 2.2 ± 1.9, second = 3.5 ± 2.2, third = 4.0 ± 2.8) who finished on the podium. The findings may provide useful information to coaches and sports scientists in the planning and implementation of specific training interventions. Furthermore, the detail of first upwind characteristics (time, distance, board speed and manoeuvres) could be used to enhance the ecological validity of laboratory-based testing.